Brain cutting and trimming. Issue 5 (5th April 2022) - Iwasaki, Yasushi
Abstract : The process of brain cutting followed by trimming is quite important to make adequate specimens for sufficient neuropathological observations. The protocol described herein is recommended as an optimized implementation for suitable preparation, which inevitably leads to an accurate neuropathological diagnosis. To obtain neuropathological cues, macroscopic observation of the brain before cutting presents an important opportunity. Gross examination provides a clue to the neuropathological diagnosis and shows clinicopathological correlations. Brain cutting should be preceded by a careful review of the clinical notes and consideration of the possible pathological diagnosis. Therefore, the medical staff associated with the patient should attend the procedure to provide clinical information. The process involves removing the brainstem and cerebellum from the cerebrum, sectioning the cerebrum, removing the cerebellum from the brainstem, and sectioning the cerebellum, brainstem and spinal cord followed by trimming. Trimming should be performed in accordance with the internationally accepted guidelines for the pathological diagnosis of different types of neurodegenerative diseases. In each stage acquiring clear photographs is significant, the observations must be concisely recorded, and which side of the specimen is to be sliced and stained has to be indicated. Additionally, it is necessary to photograph all trimmed tissues to assist with orientation of the brain in later assessments. The three‐dimensional structure and individual differences have to be considered. These skills are essential, and knowledge of neuropathology, neurology and neuroanatomy is required for appropriately cutting and trimming of the brain.